Empirical Analysis of Critical Thinking in Electrical Engineering and Computer Science Courses - Asif, Hafiz M.; Karim Sadiq, Mohamed Abdul; Kausar, Firdous; Ahmad, Afaq (Journal of Engineering Education Transformations, 2025)
In teaching and learning, the effectiveness of pedagogies centers around a range of teaching techniques. Adapting the techniques encompasses a comprehensive guide for teachers, structured and whole-class group work, guided learning, assessment practice, and individual activity. Creating a deliberate and effective pedagogy in teaching and learning is a key, ongoing improvement process that helps students learn more effectively and develop high order thinking skills. Various pedagogies can be found in the research articles that have been established for the successful implementation of teaching and learning strategies. Critical Thinking (CT) is a problem-solving pedagogy to make good decisions resulting in appropriate outcomes. In the current work, we use a guided CT pedagogy to apply most of its standards and elements to different science and engineering subjects to improve the targeted outcome of the students’ learning. The embedded model was sketched in detail for each subject and analyzed as per the actual outcomes of the targeted objectives.